INDUSTRIAL ENGINEERING FOR HALAL MANUFACTURING PROCESSES: OPTIMIZING PLANT LAYOUT TO PREVENT CROSS-CONTAMINATION (NAJIS) - Muhammad Umar Kelibia; Mona Al Johani; Charlotte Harris (Journal of Moeslim Research Technik, 2025)
The halal industry plays a critical role in global food production, ensuring that products adhere to strict religious guidelines regarding cleanliness and purity. One of the key challenges in halal manufacturing processes is preventing cross-contamination, particularly the contamination of halal products with Najis (impure substances). A crucial aspect of this challenge lies in the design of plant layouts, which must be optimized to reduce the risk of contamination during production. This research aims to investigate how industrial engineering principles can be applied to optimize plant layout in halal manufacturing settings, focusing on preventing cross-contamination. The study employs a combination of simulation modeling and expert consultations to assess current plant layouts and propose improvements. The results show that a well-designed plant layout, incorporating designated areas for halal and non-halal products, along with streamlined workflow patterns, significantly reduces the risk of Najis contamination. Additionally, implementing proper separation of production lines, storage areas, and personnel flow further enhances product safety and compliance with halal standards. The study concludes that optimizing plant layout is an effective strategy for ensuring halal product integrity, and such improvements can be adapted across various manufacturing sectors. These findings provide valuable insights for halal food producers seeking to enhance quality control and prevent contamination